2015
DOI: 10.1007/s00299-015-1756-2
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Miscanthus lutarioriparius NAC gene MlNAC5 confers enhanced drought and cold tolerance in Arabidopsis

Abstract: MLNAC5 functions as a stress-responsive NAC transcription factor gene and enhances drought and cold stress tolerance in transgenic Arabidopsis via the ABA-dependent signaling pathway. NAC transcription factors (TFs) play crucial roles in plant responses to abiotic stress. Miscanthus lutarioriparius is one of Miscanthus species native to East Asia. It has attracted much attention as a bioenergy crop because of its superior biomass productivity as well as wide adaptability to different environments. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 53 publications
6
40
0
Order By: Relevance
“…One of the best studies that reported the potential application of NAC genes in agriculture is the work of Hu et al (2006), who reported that transgenic rice plants overexpressing SNAC1 exhibited enhanced drought tolerance without yield penalty. Since then, an increasing number of studies, including transgenic or correlation analyses, have provided strong evidence for the correlation between NAC gene expression and drought-tolerant capacity of various crops (Nakashima et al, 2007; Zheng et al, 2009; Xue et al, 2011; Thao et al, 2013; Thu et al, 2014a; Zhu et al, 2014; Yang et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…One of the best studies that reported the potential application of NAC genes in agriculture is the work of Hu et al (2006), who reported that transgenic rice plants overexpressing SNAC1 exhibited enhanced drought tolerance without yield penalty. Since then, an increasing number of studies, including transgenic or correlation analyses, have provided strong evidence for the correlation between NAC gene expression and drought-tolerant capacity of various crops (Nakashima et al, 2007; Zheng et al, 2009; Xue et al, 2011; Thao et al, 2013; Thu et al, 2014a; Zhu et al, 2014; Yang et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In plants, NAC genes regulate a variety of plant developmental processes, including floral morphogenesis [24], root development [25], leaf senescence [26, 27], stress-inducible flowering induction [28], seed development [29] and fiber development [30]. NAC domain proteins have also been implicated in plant abiotic stresses and defense responses, such as salt [31, 32], wounding [33], cold [34], and particularly drought [31, 32, 35]. For example, ANAC019, ANAC055, ANAC072 and ATAF1 regulate the expression of stress-responsive genes under drought stress in Arabidopsis [36, 37].…”
Section: Introductionmentioning
confidence: 99%
“…For example, ATAF1 is strongly responsive to ABA and dehydration. (Puranik et al, 2013), and Miscanthus lutarioriparius Liu ex Chen & Renvoize ( Ji et al, 2014;Yang et al, 2015). RD26/ANAC072 plays a key role in the regulation of both abiotic and hormone signaling, induced by ABA, methyl jasmonate (MeJA), and salicylic acid (SA), in addition to salt and drought stresses .…”
Section: Cloning Characterization and Expression Analysis Of Eight mentioning
confidence: 99%
“…(Zhu et al, 2015), Populus trichocarpa L. (Hu et al, 2010), Setaria italica (L.) P. Beauv. (Puranik et al, 2013), and Miscanthus lutarioriparius Liu ex Chen & Renvoize ( Ji et al, 2014;Yang et al, 2015). Although, NAC genes studies have been extensively studied in model plants or crop species, such as Arabidopsis, soybeans, grapevines, and rice, the identification and functional characterization of stress-related NAC TFs from other plants remains interesting and would provide more insights in revealing the mechanism of NAC-regulated biological processes.…”
mentioning
confidence: 99%